Volume 5: Turbo Expo 2003, Parts a and B 2003
DOI: 10.1115/gt2003-38582
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coolant Density Ratio on Film Cooling Performance on a Vane

Abstract: Film cooling performance was studied on a simulated turbine vane model with an objective of determining how much the coolant density ratio affects this performance. Experiments were conducted using coolant density ratios of 1.8 and 1.2. The purpose of the study was to determine if tests done at small density ratios (which is often more viable in a laboratory) can give reasonable predictions of performance at more realistic large density ratios. Furthermore, appropriate scaling parameters were determined. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The distributions of η were similar for both DRs, but the DR = 1.8 coolant had a peak film effectiveness ofη = 0.38, whereas for DR = 1.2 the peak was η = 0.32. This may be attributed to better lateral distribution of the high-density coolant as noted by Sinha et al 12 Scaling of film effectiveness performance on simulated turbine airfoils was investigated by Cutbirth and Bogard 13 for the showerhead and pressure side of a vane, and by Ethridge et al 14 for the suction side of a vane. Showerhead cooling for low and high mainstream turbulence levels, T u = 0.5% and 20% respectively, was studied by Cutbirth and Bogard 13 for coolant DR = 1.2 and 1.8.…”
Section: Scaling Of Film-cooling Performance With Varying Drmentioning
confidence: 96%
See 1 more Smart Citation
“…The distributions of η were similar for both DRs, but the DR = 1.8 coolant had a peak film effectiveness ofη = 0.38, whereas for DR = 1.2 the peak was η = 0.32. This may be attributed to better lateral distribution of the high-density coolant as noted by Sinha et al 12 Scaling of film effectiveness performance on simulated turbine airfoils was investigated by Cutbirth and Bogard 13 for the showerhead and pressure side of a vane, and by Ethridge et al 14 for the suction side of a vane. Showerhead cooling for low and high mainstream turbulence levels, T u = 0.5% and 20% respectively, was studied by Cutbirth and Bogard 13 for coolant DR = 1.2 and 1.8.…”
Section: Scaling Of Film-cooling Performance With Varying Drmentioning
confidence: 96%
“…This may be attributed to better lateral distribution of the high-density coolant as noted by Sinha et al 12 Scaling of film effectiveness performance on simulated turbine airfoils was investigated by Cutbirth and Bogard 13 for the showerhead and pressure side of a vane, and by Ethridge et al 14 for the suction side of a vane. Showerhead cooling for low and high mainstream turbulence levels, T u = 0.5% and 20% respectively, was studied by Cutbirth and Bogard 13 for coolant DR = 1.2 and 1.8. They found that film effectiveness for low and high mainstream turbulence levels were most similar when compared at similar M * , where M * is the blowing ratio defined using the airfoil approach velocity, rather than the local velocity.…”
Section: Scaling Of Film-cooling Performance With Varying Drmentioning
confidence: 96%
“…8 does not match the zero point at T ini − T W = 0 as it should from Eqn. (14), although the difference is small. Possible influences might come from a slight thermal drift of the IR-signal during the transient, from changed radiation conditions during the cooling and heating phase and from 3Dconduction effects within the measurement period inside the test plate that are not considered in the transient data processing.…”
Section: Heat Transfer Coefficient Ratio H F /Hmentioning
confidence: 80%
“…Thereby the coolant might be cooled down to low temperatures (e.g. Cutbirth and Bogard [14], Bell et al [7]) or the mainstream heated to the appropriate temperature levels (e.g. Gritsch et al [2], Baldauf et al [15], Ligrani et al [5], Saumweber and Schulz [3]).…”
Section: Introductionmentioning
confidence: 99%
“…These tests were for smooth, flat surfaces. Tests for a vane leading edge, pressure side and highly curved suction side showed similar film effectiveness for low and high density coolant, but the low density ratio coolant has 10% lower adiabatic effectiveness in some cases [28,29].…”
Section: Influence Of Density Ratiomentioning
confidence: 99%